Accelerated non-linear destruction of the earth's crust - E. V. Artyushkov (Discrete Dynamics in Nature and Society)
The upper part of the Earth—the lithospheric layer, ∼100 km thick, is rigid. Segments of this spherical shell–lithospheric plates are drifting over a ductile asthenosphere. On the continents, the lithosphere includes the Earth's crust, ∼40 km thick, which is underlain by peridotitic rocks of the mantle. In most areas, at depths ∼20–40 km the continental crust is composed of basalts with density ∼2900kg m−3. At temperature and pressure typical for this depth, basalts are metastable and should transform into another assemblage of minerals which corresponds to garnet granulites and eclogites with higher densities 3300–3600 kg m−3. The rate of this transformation is extremely low in dry rocks, and the associated contraction of basalts evolves during the time ≥108 a. To restore the Archimede's equilibrium, the crust subsides with a formation of sedimentary basins, up to 10–15 km deep.